Analisis Faktor-Faktor yang Memengaruhi Minat Masyarakat Kota Jakarta terhadap Pinjaman Online Ceria BRI - Sarah Maulidina; Rina Hermawati (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2024)
Technological progress is developing rapidly in various sectors, one of which is the financial sector, commonly known as financial technology (fintech). We expect financial technology, an innovation from the financial industry, to solve various financial service problems. One form of financial transaction in financial technology services is online peer-to-peer lending or online loans. Users of online loan services increase every year because of the speed and convenience offered compared to conventional online loans, including those explicitly provided for BRI customers, namely Ceria. This research aims to identify the factors, particularly cultural and social ones, that motivate individuals to use Ceria BRI online loans. The study employs a qualitative approach, gathering data through interviews, observation, and literature review. The results of this study explain that people use online loans for urgent needs and lifestyle fulfillment. Social and cultural factors also significantly influence the use of online loans among Jakarta's residents.